Investigating the Effects of Ionospheric Scintillation on Multi‐Frequency BDS‐2/BDS‐3 Signals at Low Latitudes - Hang Liu; Xiaodong Ren; Xiaohong Zhang; Dengkui Mei; Pengxin Yang (Space Weather)
Abstract Ionospheric scintillation could seriously disrupt the signal tracking of the global navigation satellite systems (GNSS), further causing positioning accuracy degradation or unavailability. BeiDou navigation satellite system (BDS), a newly developed GNSS by China, has begun to provide global positioning, navigation, and timing service. The objective of the present study is to investigate the effects of ionospheric scintillation on BDS‐2 and BDS‐3 multi‐frequency signals. Ionospheric scintillation monitor receiver data from four monitors in Brazil were collected from October 2021 to May 2022. The results illustrate that S4(B2) and S4(B3) linearly increase with S4(B1) for S4(B1) ≤ 0.6, which is consistent with weak scattering theories, and average experimental ratios of S4(B2)/S4(B1), S4(B3)/S4(B1), and S4(B2)/S4(B3) are less than corresponding theoretical ones by 6.1%, 4.4%, and 1.9%, respectively. Meanwhile, as S4 values increase, lower‐frequency scintillation saturates earlier than higher ones, and the probability of ionospheric scintillation events on B2 and B3 signals is approximately twice (S4 ≥ 0.7) as B1 signals in the equatorial ionization anomaly (EIA) regions. To alleviate the undesirable effects of missing data on GNSS positioning, we first investigate the inter‐frequency relationship and distribution probability of two significant spectral parameters, that is, T (the spectral strength of the phase noise at 1 Hz) and p (the spectral slope of the phase power spectral density) in the tracking jitter model among three BDS frequencies. Results show that the performances among B1, B2, and B3 frequencies have a higher correlation respectively, and their values for B2 and B3 signals are more susceptible to be impacted by ionospheric scintillation.